PERUBAHAN ORGANISASI: MENGATASI RESISTENSI ATAS PERUBAHAN - Musadad, Musadad; Hayadi, Herawan; Ali Yusuf, Furtasan (Desanta Publisher, 2024)
Organizational change is one thing that organizations cannot avoid. A dynamic organizational environment and high public demands for good quality services make public organizations have to be able to adjust to change. But unfortunately the changes that occurred are not always well received, and in fact there is a resistance. Through a post positivist approach, this qualitative research seeks to analyze how public sector organizations are able to overcome the resistance of existing changes so that changes can be carried out properly and successfully achieve the desired goals. Analysis is done through literature review on several books, publications, reports or relevant news. The results of the analysis indicate that the resistance of public organizations can be avoided by the readiness of the organization to deal with changes and supported by all members of the organization, especially leaders as drivers who will bring the organization from the status quo towards the desired change. In the level of practice these efforts can be carried out by building the mental readiness of the apparatus to always be ready to face changes and be balanced with the government's ability to make responsive change policies.